Spiritualitas dan Religiusitas Pada Pasien Kanker - Erwin Wiksuarini; Muhammad Amrullah; Beti Haerani; Fuji Khairani (Institut Citra Internasional, 2022)
Spirituality is something that is very important to be realized in the health service setting and has a positive impact on cancer patients, especially in the lives of cancer patients themselves. Spirituality can reduce depressive symptoms and improve quality of life in cancer patients. A phenomenon that is still happening today is that many health services only focus on physical problems without paying attention to the psychological and spiritual problems of their patients. So that data on spirituality and religiosity in Indonesia is still not comprehensive. The purpose of the research this is to find out how the image of spirituality and religiosity in cancer patients. Deep method study This study used a quantitative descriptive design with a cross-sectional approach which was taken using accidental sampling which was carried out from early February to early April 2022 with a total sample of 115 cancer patients treated at the West Nusa Tenggara Provincial General Hospital. Resultsfrom research This shows that the average cancer patient has high spirituality with an average score of 98.81 and the highest is 120. Producing a religious value of well being is higher than the existential well being score with an average value of 52.09. The conclusion from this study is that the majority of cancer patients always worship according to their beliefs, this is shown by 91% of cancer patients who always worship according to their respective beliefs.